1996
DOI: 10.1177/082585979601200107
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusions in Advanced Hematological Malignancies: A Position Paper

Abstract: Treatment of patients with advanced-stage hematological malignancies (HM) includes frequent transfusions. Given present limited hospital budgets, administrative pressure is increasing on hematology services to limit the cost of these transfusions. An expert multidisciplinary panel involved in hematology formed a working party to draw up a series of proposals, including definitions of advanced stage disease and the indications for platelet transfusion. Their proposals included: (a) Platelet transfusions are ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…With regards to advanced cancer, platelet transfusion is seen as symptom control and needs to be on a case-by-case basis [7,14]. The administration of platelet transfusions at home is considered safe, feasible and is to be encouraged [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to advanced cancer, platelet transfusion is seen as symptom control and needs to be on a case-by-case basis [7,14]. The administration of platelet transfusions at home is considered safe, feasible and is to be encouraged [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…fatigue, dyspnoea, bleeding, infections, mucositis, delirium, drowsiness, nausea and vomiting). 8,25,27,28,47,50,62,64,[66][67][68]82,90,92,95,98,100,102,103,108,113 Two studies 8,92 compared the symptoms experienced by patients with haematological malignancies and nonhaematological neoplasms, reporting that symptoms in haematological malignancies patients are often more severe. Pain is frequent in haematological malignancies patients and is the most common reason for referral to palliative care, particularly in patients with multiple myeloma.…”
Section: Patient Clinical Characteristicsmentioning
confidence: 99%
“…The use of blood products and routine blood counts in patients with haematological malignancies in the palliative stage remains controversial, as noted by many authors. 28,64,65,70,96 One study found that emotional distress in patients with haematological malignancies is often severe. 51 Several authors even compare the level of emotional distress in haematological malignancies to post-traumatic stress disorder, a finding that underscores its severity.…”
Section: Patient Clinical Characteristicsmentioning
confidence: 99%
“…Patients with chronic autoimmune thrombocytopenia can tolerate platelet counts in the 5-10,000/µl range for long periods of time. Platelet transfusion in the setting of advanced cancer should be on a case-by-case basis with the aim of controlling symptoms [106]. A single unit of platelets should increase the platelet count in an average adult by approximately 6,000-10,000/µl, assuming normal splenic pooling.…”
Section: Blood Productsmentioning
confidence: 99%
“…The short half-life of platelets, which decreases further as their counts drop, limits their usefulness in severely thrombocytopenic patients with end-stage disease. Lassauniere and colleagues have proposed criteria for platelet transfusions in patients with advanced hematologic malignancies [106]. These criteria include continuous bleeding of the mouth or gums, epistaxis, extensive and painful hematomas, severe headaches, or disturbed vision of recent onset, as well as continuous bleeding through the gastrointestinal, gynecological, or urinary systems.…”
Section: Blood Productsmentioning
confidence: 99%